2004
DOI: 10.1002/gcc.20078
|View full text |Cite
|
Sign up to set email alerts
|

MDS/AML‐associated cytogenetic abnormalities in multiple myeloma and monoclonal gammopathy of undetermined significance: Evidence for frequent de novo occurrence and multipotent stem cell involvement of del(20q)

Abstract: Multiple myeloma (MM) and monoclonal gammopathy of undetermined significance (MGUS) are characterized cytogenetically by 14q32 rearrangements, -13/13q-, and various trisomies. Occasionally, karyotypic patterns characteristic of myelodysplastic syndrome (MDS)/acute myeloid leukemia (AML) occur in MM, often signifying therapy-related (t)-MDS/t-AML. Comparison of cytogenetic features in all published MMs (n = 993) and t-MDS/t-AML post-MM (n = 117) revealed significant differences in complexity and ploidy levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Cytogenetic analysis and aCGH showed that the karyotype and the genomic profile of the majority of these cases was complex. Other studies had reported that cytogenetic changes were more frequent in PCL than in MM (Gutierrez et al, 2001;Smadja et al, 2003;Nilsson et al, 2004). Our data confirms that some PCL cases are extremely complex, although some show relatively simple changes.…”
Section: Discussionsupporting
confidence: 93%
“…Cytogenetic analysis and aCGH showed that the karyotype and the genomic profile of the majority of these cases was complex. Other studies had reported that cytogenetic changes were more frequent in PCL than in MM (Gutierrez et al, 2001;Smadja et al, 2003;Nilsson et al, 2004). Our data confirms that some PCL cases are extremely complex, although some show relatively simple changes.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have detected del(20q) in stem cells with both myeloid and lymphoid differentiation capabilities. 24,25 Several non-neoplastic conditions have also been associated with del(20q), including idiopathic thrombocytopenic purpura, 26 pure red blood cell aplasia, 27 Schwachman-Diamond syndrome, 24 and idiopathic cytopenia. 28 In prior studies of cases of myeloid neoplasms, the presence of del(20q) alone or accompanied with one other chromosomal abnormality has been associated with favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In plasmacytoma CD34 + /CD38 + progenitor cells and granulocytic cells can be of the same clonal origin [57]. A common clonal origin has been demonstrated in post-plasmacytoma MDS [72], which is a remarkable setting because, in this context, a secondary therapy-associated MDS is usually considered [25,33,52,66].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously suspected [11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91], but not systematically evaluated and proven, that Ph – MPN-B-CLL is the most common combination in patients with two different haematological neoplasms (fig. 3; online suppl.…”
Section: Discussionmentioning
confidence: 99%